Sistem Pakar Identifikasi Kerusakan pada Budidaya Lebah Madu (Apis Cerena) Menggunakan Metode Certainty Factor: Array - Eka, Muhammad (Universitas Harapan Medan, 2020)
Expert systems which are part of artificial intelligence and have an important role in the development of information technology in various fields, expert systems answer all the problems we have faced by providing the right solutions based on one's expertise in a field. The expert system for identifying damage to the management of Apis Cerana bee cultivation is a practical solution in treating and repairing damage caused by pests and diseases. Identification of damage to the management of Apis Cerana bee cultivation using a certainty factor method, which will be assessed for its accuracy level by an expert. The result of using certainty factor method is definite proof or not a fact or diagnosis of damage caused by pests and diseases in Apis Cerana bee cultivation. The percentage level of certainty of damage to the management of Apis Cerana beekeeping is obtained and determined by an expert and implemented into a Web-based system.